Platinum Nanopeapods: Spatial Control of Mesopore Arrangements by Utilizing a Physically Confined Space. Issue 35 (19th July 2013) - Takai, Azusa; Sakamoto, Yasuhiro; Terasaki, Osamu; Yamauchi, Yusuke; Kuroda, Kazuyuki
<x xml:space="preserve">Abstract</x> Spherical mesopores: Mesoporous Pt rods containing cage‐type mesopores were prepared with porous anodic alumina membranes (PAAMs). It is noteworthy that spherical mesopores are aligned in the rods due to physical confinement by the PAAM channels. Both the mesopore alignment and the morphological control are realized simultaneously, which could be important for bottom‐up approaches to nanometals with desirable structural features (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>